On the Debt to GDP Ratio in Monopolistic Competition - Tanaka Yasuhito (Folia Oeconomica Stetinensia)
Many people in Japan and other countries believe that national finances will not stand still and will go bankrupt if deficits continue at present level. It is like a religion. In this paper, however, we prove that this religion is wrong by using a simple mathematical model.